Guest Editorial Foreword to the Special Issue of IHC 2017 - Gasparini, Isabela; Piccolo, Lara; Salgado, Luciana; Zaina, Luciana; Pereira, Roberto (Journal on Interactive Systems, 2018)
Foreword to the Special Issue of IHC 2017